3D Biosilica Scaffolds from Melophlus sarasinorum and Xestospongia testudinaria Indonesian Sponges are Biocompatible for Cell Growth and Differentiation of Human Wharton’s Jelly Mesenchymal Stem Cell in Bone Tissue Engineering - Soraya Rahmanisa; Ekavianty Prajatelistia; Indra Wibowo; Anggraini Barlian (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Biosilica derived from Indonesian marine sponge Melophlus sarasinorum and Xestospongia testudinaria is one of the biomaterials that can be developed together with synthetic polymer as a composite. Poly E-caprolactone (PCL) used as a composite role as an osteoconductive material together with biosilica and also tailored the slow rate of degradation in the body. This study aimed to create a biocompatible biosilica-based scaffold and supports osteogenic differentiation of human Wharton's Jelly mesenchymal stem cell (hWJ-MSCs).METHODS: Biosilica was extracted from M. sarasinorum and X. testudinaria with the acid digestion method. Scaffold was prepared using the salt leaching method. The composite scaffolds were made from seven different biosilica extract and PCL. All of the scaffolds were tested for the cell morphology, Fourier-transform infrared spectroscopy (FTIR), immunocytochemistry, and cytotoxicity.RESULTS: Composite scaffolds of 50% M. sarasinorum and X. testudinaria increased the cell viability and supported the cell growth within 14 days, whereas the osteogenic differentiation can be seen by the presence of collagen type 1 in day 12 based on immunocytochemistry result.CONCLUSION: The biosilica scaffolds from PCL+50% M. sarasinorum and PCL+50% X. testudinaria were promising 3D scaffolds for potential application in bone tissue engineering. In conclusion, this study shows evidence for the osteogenic differentiation of hWJ-MSC, which might be developed for bone tissue engineering.KEYWORDS: sponge, biosilica, scaffold, osteogenesis, stem cell